Novel ITGB6 variants cause hypoplastic-hypomineralized amelogenesis imperfecta and taurodontism: characterization of tooth phenotype and review of literature - Kanokwan Sriwattanapong; Thanakorn Theerapanon; Lawan Boonprakong; Anucharte Srijunbarl; Thantrira Porntaveetus; Vorasuk Shotelersuk (Nature Publishing Group, 2023)
Abstract Objectives To characterize phenotype and genotype of amelogenesis imperfecta (AI) in a Thai patient, and review of literature. Materials and methods Variants were identified using trio-exome and Sanger sequencing. The ITGB6 protein level in patient's gingival cells was measured. The patient's deciduous first molar was investigated for surface roughness, mineral density, microhardness, mineral composition, and ultrastructure. Results The patient exhibited hypoplastic-hypomineralized AI, taurodontism, and periodontal inflammation. Exome sequencing identified the novel compound heterozygous ITGB6 mutation, a nonsense c.625 G > T, p.(Gly209*) inherited from mother and a splicing c.1661-3 C > G from father, indicating AI type IH. The ITGB6 level in patient cells was significantly reduced, compared with controls. Analyses of a patient's tooth showed a significant increase in roughness while mineral density of enamel and microhardness of enamel and dentin were significantly reduced. In dentin, carbon was significantly decreased while calcium, phosphorus, and oxygen levels were significantly increased. Severely collapsed enamel rods and a gap in dentinoenamel junction were observed. Of six affected families and eight ITGB6 variants that have been reported, our patient was the only one with taurodontism. Conclusion We report the hypoplasia/hypomineralization/taurodontism AI patient with disturbed tooth characteristics associated with the novel ITGB6 variants and reduced ITGB6 expression, expanding genotype, phenotype, and understanding of autosomal recessive AI.